An Analysis of Schwa Distribution in Sasak Language Ngeno-Ngene Dialect Spoken in Kotaraja Village East Lombok - Langkawi, Nirwana; Ahmadi, Nur; Arafiq, Arafiq (Jurnal Ilmiah Pendidikan Indonesia, 2020)
This study is aimed to (a) find out schwa distribution in Sasak language ngeno-ngene dialect spoken in Kotaraja village East Lombok, (b) to find out underlying and surface representation of schwa in Sasak language ngeno-ngene dialect spoken in Kotaraja village East Lombok and (c) to derive rule underlying schwa in Kotaraja Phonology. This research applied descriptive qualitative method. The source of data was all linguistics expressions spoken by Kotaraja native speakers consisting of 13.510 people. A sample language was recorded from an informant who had fulfilled some criteria. The data were collected by observing, storytelling, and recording. The result of this study shows that schwa distributes on the last syllable of word followed by k and ? sound and also on open syllable of loan word borrowed from Bahasa Indonesia. Study finds that schwa is Surface Representation originated from Underlying Representation u, I, and a depending on its distribution. Furthermore, study reveals that u and I sound become schwa sound when it’s followed by k and ? sound, and also a sound becomes ? sound when it appears on open syllable.